Characteristics of depressed suicide attempters with remitted substance use disorders. (May 2021) - Rizk, Mina M.; Galfalvy, Hanga; Miller, Jeffrey M.; Milak, Matthew; Parsey, Ramin; Grunebaum, Michael; Burke, Ainsley; Sublette, M. Elizabeth; Oquendo, Maria A.; Stanley, Barbara; Mann, J. John
Abstract: Substance use disorder (SUD) comorbidity in mood disorders increases suicide risk. Suicide attempters with active SUD appear to have distinct characteristics but little is known whether these characteristics persist during remission and if they are related to different aspects of suicidal behavior. In this study, suicide attempters with a DSM mood disorder and remitted SUD (AT+SUD) (N = 135) were compared to those without lifetime SUD (AT-SUD) (N = 219) in terms of demographic, clinical and suicidal behavioral characteristics. Factor analyses were conducted to generate subjective distress and impulsivity/aggression factors – previously identified by our group to predict suicide risk in mood disorders. Associations between these traits and SUD history and suicidal behavior characteristics were then tested. Compared with AT-SUD, AT+SUD were more likely to be male, less educated and to have a Cluster B personality disorder. AT+SUD individuals had greater impulsivity/aggression factor scores, but comparable subjective distress scores. AT+SUD made a greater number of suicide attempts, with higher lethality, despite comparable suicide intent and degree of planning with AT-SUD. Impulsivity/aggression was higher in multiple versus single attempters, but did not correlate with suicide attempt lethality. Among suicide attempters with mood disorders, a history of lifetime SUD was associated with more frequent and more lethal suicide attempts. Among other correlates of lifetime SUD in this sample, impulsive/aggressive traits may explain greater frequency of suicide attempts. The results underscore that persons with mood disorders and lifetime SUD are at particularly high risk of frequent and lethal suicide attempts where more intensive prevention efforts are warranted.